2004
DOI: 10.1098/rstb.2004.1552
|View full text |Cite
|
Sign up to set email alerts
|

A neuroscientific approach to normative judgment in law and justice

Abstract: Developments in cognitive neuroscience are providing new insights into the nature of normative judgment. Traditional views in such disciplines as philosophy, religion, law, psychology and economics have differed over the role and usefulness of intuition and emotion in judging blameworthiness. Cognitive psychology and neurobiology provide new tools and methods for studying questions of normative judgment. Recently, a consensus view has emerged, which recognizes important roles for emotion and intuition and whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 152 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…From this standpoint, also known as the intuitionism 2004), it is believed that unconscious emotional processing is responsible for the majority of the usual moral judgments and that “most of the action in moral judgment is in the automatic, affectively laden intuitions, not in conscious verbal reasoning theory” (Haidt, 2008, p.70). Therefore, the conscious and verbally expressed evaluations on actions will play a minor role when it comes to examining an individual’s normative judgment and it is thought that right versus wrong evaluative feelings regarding acts or characters happen “without any conscious awareness of having gone through steps of search, weighing evidence, or inferring a conclusion” (Haidt & Bjorklund, 2008, p. 188).…”
Section: Discussionmentioning
confidence: 99%
“…From this standpoint, also known as the intuitionism 2004), it is believed that unconscious emotional processing is responsible for the majority of the usual moral judgments and that “most of the action in moral judgment is in the automatic, affectively laden intuitions, not in conscious verbal reasoning theory” (Haidt, 2008, p.70). Therefore, the conscious and verbally expressed evaluations on actions will play a minor role when it comes to examining an individual’s normative judgment and it is thought that right versus wrong evaluative feelings regarding acts or characters happen “without any conscious awareness of having gone through steps of search, weighing evidence, or inferring a conclusion” (Haidt & Bjorklund, 2008, p. 188).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deontologists such as Immanuel Kant propose universal moral principles that should be observed despite ‘the greater good’ and determine the moral worth of an action by examining its inherent value (for review [57] ). A study of normative judgments in the law has shown that juries' decisions are not entirely dispassionate and rationally-based but can be strongly influenced by emotion [58] . In economics, emotion has also been found to interfere with the rational motivation of obtaining maximal profit predicted by neoclassical economics and game theory [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Anglo-American jurisprudence distinguishes between reason-based law and a natural law based on what a “reasonable person” would do in like circumstance. 169 Paradoxically, under the law a “reasonable person” is someone who actually responds to intact moral emotions; therefore, the proof that these patients lack the faculties of a “reasonable person” is the sociopathic behaviors themselves. These considerations demand a reappraisal of the how we view culpability and criminal violations among brain-injured patients.…”
Section: Discussionmentioning
confidence: 99%